INTEGRITAS PEGAWAI DALAM PEMBERIAN PELAYANAN - Febri Yuliani, Mudir Johan, Sujianto, (Jurnal Ilmu Administrasi Negara, 2019)
Employee Integrity in Providing Services. This study aims to determine the integrity of employees in service at the Head Office of the City of Pekanbaru Rumbai Pesisir. Type of qualitative research. Research informants were employees of the Head Office of the City of Pekanbaru Rumbai Pesisir. Data collection techniques are interviews, observation and documentation. Data analysis is reduction, clarification and verification. The results of this study have not been wholeheartedly seen by employees in providing services, unfair employees in providing services, not yet responsive employees in serving the community, and not yet how employees keep their promises and are responsible for providing services.